DINAMIKA PERKEMBANGAN KOTA SALA 1746-2011 - , Qomarun, Ir.,MM.; , Dr. Ir. Arya Ronald ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The background of this study is the phenomena that the urban spaces of Sala experienced up and down because of urban disasters, especially of urban social disaster (USD). To explore the root of that problem, the research made two major studies: urban morphology and urban disaster. This study uses rationalistic paradigm, while the research method uses interpretive-historical. Afterwards, this study found three main findings as follows: (1) impulsive model as an urban development dynamic type